2006
DOI: 10.1111/j.1083-6101.2001.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

The Internet for the Blind and Visually Impaired

Abstract: A qualitative study of fifteen blind or visually impaired persons and sixteen professionals who work with blind and visually impaired persons sought to explore the potential role of the Internet in information provision for this group of people. Traditional forms of access to information such as print have meant that people who are blind and visually impaired have more difficulty in accessing the same range of information that people who are sighted take for granted. Increasingly, computers are being viewed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…According to , online communities are an important means of communication for disabled people due to its removal from the conventions and confinements of offline reality. As Huffaker, and Calvert (2005) suggest, the internet is a space whereby 'the power of the gaze becomes displaced by a textually oriented medium' (Bowker & Tuffin 2002, p.340), affording disabled people agency over important aspects of identity construction (Guo, Bricout, and Huang 2005;Stamou, Alevriadou, and Soufla 2016;Williamson et al 2001). Research by Kang, Brown, and Kiesler (2013) also presents anonymity as a tool for individuals to manage their online social relationships, particularly if they found this difficult offline, while for others, anonymity is sought to preserve their offline relationships by keeping their online persona separate from their constructed offline image (Bargh, McKenna, and Fitzsimons 2002).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…According to , online communities are an important means of communication for disabled people due to its removal from the conventions and confinements of offline reality. As Huffaker, and Calvert (2005) suggest, the internet is a space whereby 'the power of the gaze becomes displaced by a textually oriented medium' (Bowker & Tuffin 2002, p.340), affording disabled people agency over important aspects of identity construction (Guo, Bricout, and Huang 2005;Stamou, Alevriadou, and Soufla 2016;Williamson et al 2001). Research by Kang, Brown, and Kiesler (2013) also presents anonymity as a tool for individuals to manage their online social relationships, particularly if they found this difficult offline, while for others, anonymity is sought to preserve their offline relationships by keeping their online persona separate from their constructed offline image (Bargh, McKenna, and Fitzsimons 2002).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Williamson, Wright, Schauder, and Bow (2001) observed a sense of online community amongst people who are blind or vision impaired and found that it provided a means to create social ties with other members. Cummings, Sproull, and Kiesler (2002) looked at an online self-help group for people with hearing loss and found those individuals who received low general social support experienced benefits from online emotional and informational support.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies have shown current web accessibility to be less than optimal [11,18,20]. Despite significant advances in assistive technologies, blind and visually impaired Internet users continue to encounter barriers when accessing web content [9,29,33].…”
Section: Introductionmentioning
confidence: 99%